Definitive tumor directed therapy confers a survival advantage for metachronous oligometastatic HPV-associated oropharyngeal cancer following trans-oral robotic surgery. (October 2021) - Wright, Christopher M.; Lee, Daniel Y.; Shimunov, David; Carmona, Ruben; Barsky, Andrew R.; Sun, Lova; Cohen, Roger B.; Bauml, Joshua M.; Brody, Robert M.; Basu, Devraj; Rassekh, Christopher H.; Chalian, Ara A.; et al.
Highlights: Metastasis are uncommon following resection of HPV-associated oropharynx cancer. Burden of disease at metastatic presentation is strongly associated with survival. For oligometastasis, definitive tumor directed therapy is associated with improved survival. Definitive tumor directed therapy obviated the need for chemotherapy in 40% of patients. Abstract: Objectives: To assess the prognostic significance of oligometastatic versus polymetastatic disease in human papillomavirus (HPV)-associated oropharyngeal squamous cell carcinoma (OPSCC), and to evaluate the impact of definitive tumor directed therapy on the survival outcomes for patients with oligometastatic disease when compared to systemic therapy. Materials and Methods: This was a retrospective observational cohort study of patients with HPV-associated OPSCC who developed distant metachronous metastatic disease after undergoing initial primary surgical management from 2008 to 2017. We classified patients based on the extent of metastatic disease [Oligometastatic (≤5 metastases) and polymetastatic (>5 metastases)], and the initial treatment of metastatic disease [definitive tumor directed therapy (all metastases treated with surgery or radiotherapy) versus upfront systemic therapy]. Results: Among 676 patients undergoing primary surgical management for HPV-associated OPSCC, 39 patients (5.8%) developed metastases after a median follow-up of 29.6 months (range 4.5–127.0). Of the 34 metastatic patients who met study criteria, 26 (76.5%) were oligometastatic and 8 (23.5%) were polymetastatic. Oligometastatic patients had improved median overall survival (OS) compared to polymetastatic patients (47.9 vs. 22.7 months, p = 0.036). For oligometastatic patients, definitive tumor directed therapy was associated with an improved median progression free survival (not reached vs 6.13 months, p = 0.001) and median OS (not reached vs 40.7 months, p = 0.004). Conclusion: In a cohort of patients surgically treated for HPV-associated OPSCC, metachronous metastatic disease was uncommon and, in most cases, considered oligometastatic. Oligometastasis portends a favorable prognosis and definitive tumor directed therapy may be associated with improved overall survival in these patients. Future multi-institutional efforts are warranted to further demonstrate the impact of definitive tumor directed therapy on disease outcomes.